Java stream fusion: Adapting FP mechanisms for an OO setting - Ribeiro, Francisco (2019)
In this paper, we show how stream fusion, a program transformation technique used in functional programming, can be adapted for an Object-Oriented setting. This makes it possible to have more Stream operators than the ones currently provided by the Java Stream API. The addition of more operators allows for a greater deal of expressiveness. To this extent, we show how these operators are incorporated in the stream setting. Furthermore, we also demonstrate how a specific set of optimizations eliminates overheads and produces equivalent code in the form of for loops. In this way, programmers are relieved from the burden of writing code in such a cumbersome style, thus allowing for a more declarative and intuitive programming approach.